Analisis Kata Serapan Bahasa Arab Dalam Tindak Tutur Masyarakat Melayu Bengkalis - Zurin , Khaizatul; Ulfa, Marhamah; Mardiana, Mardiana (AL-IMAM: Journal on Islamic Studies, Civilization and Learning Societies, 2024)
This study aims to analyse the absorption of Arabic words in the speech acts of the Malay community in Bengkalis. The research method used is qualitative with a descriptive-analytical approach. Data were collected through interviews, and observations and then analysed using content analysis techniques. The results showed that Arabic absorption words have a significant role in the speech acts of the Bengkalis Malay community. The use of these absorption words reflects the influence of Arabic culture in the daily life and communication of the local community. In addition, Arabic absorption words also enrich the vocabulary and linguistic expressions in the daily language of the Bengkalis Malay community. This research provides an in-depth understanding of the dynamics of the use of Arabic words in the language and culture of the Bengkalis Malay community. The implications of these findings can be an important contribution to the study of linguistics, language anthropology, and cultural studies, as well as provide a foundation for the preservation and development of cultural and linguistic heritage in this region.